Effect of Single-Clove Garlic (Allium Sativum Var. Solo Garlic) Extract on Lipid Profile in Male Wistar Rats with Dyslipidemia” - Miranda Winda Sari Sitorus; Suandy Suandy; Linda Chiuman (Indonesian Journal of Global Health Research, 2026)
Dyslipidemia, a major risk factor for cardiovascular diseases, is characterized by abnormal lipid profiles. While conventional treatments exist, they often have side effects, leading to a growing interest in natural alternatives. Single-clove garlic (Allium sativum var. solo) contains bioactive compounds known for their antioxidant and lipid-lowering properties. This study aimed to evaluate the effectiveness of single-clove garlic extract in improving the lipid profile, including total cholesterol, triglycerides, HDL, and LDL, in dyslipidemic male Wistar rats. A quasi-experimental pre-test and post-test control group design was used with 24 male Wistar rats using purposive sampling. Dyslipidemia was induced with a high-fat diet for 40 days. The rats were divided into four groups: a positive control (simvastatin), a negative control, and two treatment groups receiving different doses of single-clove garlic extract. Lipid profiles were measured on days 7, 14, 21, and 28. Data were analyzed using one-way ANOVA and Tukey’s HSD post-hoc test. The administration of single-clove garlic extract significantly improved the lipid profile of the rats. Over 28 days, treatment groups showed a significant reduction in total cholesterol, triglycerides, and LDL levels, while HDL levels increased. These changes were comparable to those observed in the positive control group. The findings suggest that single-clove garlic extract is effective in improving the lipid profile in dyslipidemic male Wistar rats.